2020
DOI: 10.1186/s13018-020-02135-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of patient-reported outcome measures (PROMs) by orthopedic surgeons in Saudi Arabia

Abstract: Background There is increasing literature on the usefulness of patient-reported outcome measures (PROMs), but far fewer studies to determine their use by orthopedic surgeons and the barriers they face in applying PROMs in their daily clinical activity. Methods Cross-sectional study using a questionnaire that was distributed in both soft and hard copy formats to a sample of 262 orthopedic surgeons. Participants included orthopedic surgeons who are e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
(29 reference statements)
4
13
0
Order By: Relevance
“…Surgeons still perceive limited utility for PROMs in patient care, noting that they preferred talking with patients about outcomes the patient had identified as important, seeing these personalized outcomes as more meaningful rather than a numbered score that can be difficult to explain. Other studies examining perceptions of PROMs have also identified these issues [1,7,11,14,21,23,26,32,40]. To fully incorporate PROM scores into clinical care, well-designed PROM systems will need to be developed with measures that not only have good psychometric properties and strong evidence to support their use for comparisons, but also PROMs that reflect the unique outcomes desired by individual patients.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons still perceive limited utility for PROMs in patient care, noting that they preferred talking with patients about outcomes the patient had identified as important, seeing these personalized outcomes as more meaningful rather than a numbered score that can be difficult to explain. Other studies examining perceptions of PROMs have also identified these issues [1,7,11,14,21,23,26,32,40]. To fully incorporate PROM scores into clinical care, well-designed PROM systems will need to be developed with measures that not only have good psychometric properties and strong evidence to support their use for comparisons, but also PROMs that reflect the unique outcomes desired by individual patients.…”
Section: Limitationsmentioning
confidence: 99%
“…We investigated an initiative in which PROMs were systematically collected and provided via the electronic health record but were infrequently used. Questions/purposes In a qualitative study, we asked: (1) Why are PROM results not being used in clinical care when they are available to surgeons? (2) What aspects of PROMs are seen as useful for clinical care?…”
mentioning
confidence: 99%
“…However, studies examining this assumption have found limited use of PROs. Main reasons according to surgeons are a lack of knowledge on how to use PROs in daily health care, the perception that PROs do not provide actionable information, and because gathering and handling of PROs add work to an already busy schedule [31,32]. In addition, orthopaedic surgeons state that using PROs on an individual patient level is difficult based on logistical barriers (access and display issues, time required) and perceptual barriers (concerns about patients understanding, and validity and reliability of measures).…”
Section: Discussionmentioning
confidence: 99%
“…PROMs have recently been used in national registries and could be helpful in decision-making in total joint arthroplasty and as an early indicator in implant failure [20,21]. However, it is crucial to limit their use to evaluate aspects for which the scale was constructed for and to interpret their results according to their psychometric qualities [22,23]. Moreover, Gagnier et al [2] reported that no single PROM can evaluate all dimensions and have the required psychometric properties.…”
Section: Discussionmentioning
confidence: 99%